Moderasi Good Corporate Governance pada Pengaruh Intellectual Capital terhadap Kinerja Keuangan - Andi Harmoko Arifin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The condition of the domestic cement market is experiencing an oversupply so that it is in a very apprehensive condition or is on the verge of bankruptcy. Why is this happening because there is a predatory pricing policy, in which a cement company deliberately sells cement in Indonesia at a loss, so the government must also make more specific regulations governing various illegal business practices. The research objective is to analyze and test the effect of intellectual capital and on GCG, to analyze and test the effect of intellectual capital and GCG and to analyze and test the effect of intellectual capital on PT Semen Tonasa's financial performance through the GCG variable. Data collection was carried out using a survey method by selecting samples by purposive sampling among existing populations based on work units, the units of analysis in this study were organic employees, General Managers, Senior Managers, Managers and Supervisors, so that the sample used was 79 samples. In accordance with the hypothesis that has been formulated, in this study the analysis of the research data used Smart PLS (Partial Least Square) software. The results of the study show that intellectual capital has a significant positive effect on good corporate governance. intellectual capital has a significant positive effect on financial performance. good corporate governance has a significant positive effect on financial performance, and good corporate governance is able to moderate the relationship of Intellectual capital to financial performance in PT. Semen Tonasa, this shows that effective good corporate governance will increase intellectual capital and ultimately have an impact on increasing the company's financial performance.